Motherhood unveiled: examining the dynamic relationship between sleep quality and breastfeeding confidence in postpartum primiparous women in Syria: a cross-sectional study - Alaa Aldairy; Jamal Ataya; Dana Haymoun; Roula Samer Kashlan; Joudi Kouran; Nagham Amouna; Dema Adwan; Marwan Alhalabi (BMC Public Health)
Abstract Background Breastfeeding self-efficacy signifies a mother’s confidence in her ability to breastfeed. Sleep quality, on the other hand, refers to the effectiveness of sleep. Low sleep quality is a common issue faced by new mothers during the postpartum period. It remains unclear whether there is a connection between a mother’s perception of breastfeeding self-efficacy, which has a positive effect on breastfeeding, and sleep quality during the postpartum period. This study aims to determine the relationship between sleep quality and breastfeeding self-efficacy among primiparous mothers during the postpartum period, while also examining the impact of different demographic factors. Materials and methods This descriptive study included 316 primiparous women who delivered babies in Damascus, Syria. Data were gathered using a questionnaire comprising 53 questions divided into three sections: demographic information, the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), and the Pittsburgh Sleep Quality Index (PSQI). Participants’ answers were collected via telephone interviews conducted by the authors, along with an electronic version of the questionnaire that was distributed online. IBM SPSS was used to perform descriptive statistics, independent t-tests, one-way ANOVA, MANOVA, post hoc tests, and Pearson correlation analyses. A P-value of < 0.05 was considered to indicate statistical significance for all the analyses. Results A significant negative correlation emerged between maternal breastfeeding self-efficacy and PSQI scores. The gender distribution of the newborns yielded significant differences in maternal sleep quality as assessed using the PSQI but not in terms of the mean score on the BSES-SF. Maternal age was positively correlated with maternal breastfeeding self-efficacy and PSQI scores. Regarding education level and overall sleep quality, a significant difference was observed, as mothers with higher education levels tended to have lower overall sleep quality, but no relation to breastfeeding self-efficacy was detected. The multivariate analysis showed a positive correlation between breastfeeding self-efficiency and higher financial status. No significant differences were found in relation to type of delivery or infant age or residential factors. Conclusions Research findings indicated a positive correlation between the breastfeeding self-efficacy of postpartum women and their overall sleep quality, with an observed increase in breastfeeding self-efficacy as sleep quality improved.